Farmer Perception Toward the Role of Shallot (Allium Ascalonicum L) Farmer’s Group at Desa Tunganamo, Kecamatan Pantai Baru, Kabupaten Rote Ndao - Yumisa Tenu; Serman Nikolaus; I Wayan Nampa (Buletin Ilmiah Impas, 2022)
This research had been conducted at Tunganamo Village, Pantai BaruSub-District, Rote Ndao District started from June until July in 2019, with the aim to understand: (1). Farmer group characteristic at Tunganamo Village, and (2). Farmer’s perception toward the roles of Onion Farmer Group at Tunganamo Village, Pantai Baru Sub-District, Rote Ndao District. Data were collected by using a survey method. Renspondents consisted of 43 farmers, were selected randomly from 76 farmer group members. Data measured by likert scale were analyzed by both quantitative and qualitative descriptive statistics. Results of analysis indicated that: (1). The carateristics of onion farmer group located in Tunganamo Village, Pantai Baru Sub-District, Rote Ndao District as follows: there are three farmer groups existed in the research location namely Oliseu farmer group, which consisted of 24 farmers, Edene Ana farmer group which consisted of 27 farmers and Baru Terbit farmer group which consisted of 24 farmers. Those farmer groups were builded in the year of 2008, with the aim to get subsidy from government in relation to agriculture production facilities; and (2). Farmer’s perception on onion farmer group existed in Tunganamo Village, Pantai Baru Sub-District, the District of Rote Ndao was in “good category”, because the percentase of average score in reaching the maximum score was 68,46 % located in the range of 68-83 %.